2019
DOI: 10.3390/molecules24234421
|View full text |Cite
|
Sign up to set email alerts
|

Antiprotozoal Activity of Turkish Origanum onites Essential Oil and Its Components

Abstract: Essential oil of Origanum species is well known for antimicrobial activity, but only a few have been evaluated in narrow spectrum antiprotozoal assays. Herein, we assessed the antiprotozoal potential of Turkish Origanum onites L. oil and its major constituents against a panel of parasitic protozoa. The essential oil was obtained by hydrodistillation from the dried herbal parts of O. onites and analyzed by Gas Chromatography-Flame Ionization Detector (GC-FID) and Gas Chromatography coupled with Mass Spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 60 publications
3
19
0
Order By: Relevance
“…In addition, it is notable that carvacrol showed same activity of EO-Pa against P. falciparum (Figure 3), which could suggest that antiplasmodial activity is caused by the main active compound. Similar results were shown by Tasdemir et al, 59 who previously reported an IC 50 value for carvacrol of 6.4 ± 0.9 µg/mL against P. falciparum K1 strain (chloroquine-and pyrimethamine-resistant).…”
Section: Resultssupporting
confidence: 90%
“…In addition, it is notable that carvacrol showed same activity of EO-Pa against P. falciparum (Figure 3), which could suggest that antiplasmodial activity is caused by the main active compound. Similar results were shown by Tasdemir et al, 59 who previously reported an IC 50 value for carvacrol of 6.4 ± 0.9 µg/mL against P. falciparum K1 strain (chloroquine-and pyrimethamine-resistant).…”
Section: Resultssupporting
confidence: 90%
“…Tasdemir et al . assessed the antiprotozoal activity of Origanum onites against some protozoa 61 . The main components of the oil were carvacrol (70.6%), linalool (9.7%), p -cymene (7%), γ -terpinene (2.1%), and thymol (1.8%).…”
Section: Alternative Treatmentsmentioning
confidence: 99%
“…It did not show toxicity to mammalian cells. Some of these compounds were assessed individually with a decrease in their activity, suggesting that they have an additive action 61 .…”
Section: Alternative Treatmentsmentioning
confidence: 99%
“…Tasdemir et al (2019) [ 42 ] evaluated the in vitro activity of the essential oil of Turkish Origanum onites L. and its main constituents against T. cruzi . The main components found in the essential oil were carvacrol (70.6%), followed by linalool (9.7%), p -cymene (7%), γ-terpinene (2.1%), and thymol (1.8%).…”
Section: Essential Oils With Trypanocidal Activitymentioning
confidence: 99%
“…Tasdemir et al (2019) [ 42 ] also evaluated the in vitro activity of the essential oil of Origanum onites L. turco and its main constituents against T. brucei rhodesiense . The oil showed significant in vitro activity against T. brucei rhodesiense (IC 50 180 ng/mL) without causing toxicity in mammalian cells.…”
Section: Essential Oils With Trypanocidal Activitymentioning
confidence: 99%